2010
DOI: 10.1152/ajpcell.00138.2010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic amplifying pathway increases both phases of insulin secretion independently of β-cell actin microfilaments

Abstract: ]c was elevated and controlled by KCl or tolbutamide, the amplifying action of glucose was facilitated by actin depolymerization and unaffected by polymerization. Both phases of IS were larger in response to high-glucose than to tolbutamide in low-glucose, although triggering [Ca 2ϩ ]c was lower. This difference in IS, due to amplification, persisted when the IS rate was doubled by actin depolymerization or polymerization. In conclusion, metabolic amplification is rapid and influences the first as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 55 publications
11
77
0
Order By: Relevance
“…This may account for the characteristic dynamics of first phase of GIIS, which occurs rapidly, massively, and transiently. Indeed, actin-depolymerizing agents such as cytochalasin B and latrunculin B sustain massive insulin secretion from perifused pancreatic islets during application (23,45,57). It is also established that insulin is immediately, massively, and transiently secreted by K ϩ stimulation (6,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may account for the characteristic dynamics of first phase of GIIS, which occurs rapidly, massively, and transiently. Indeed, actin-depolymerizing agents such as cytochalasin B and latrunculin B sustain massive insulin secretion from perifused pancreatic islets during application (23,45,57). It is also established that insulin is immediately, massively, and transiently secreted by K ϩ stimulation (6,8).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that cytochalasin E and Clostridium botulinum C2 toxin, which are F-actin-depolymerizing agents, decrease insulin secretion (22). More recently, latrunculin B, which binds to G-actin and leads to F-actin depolymerization, was shown to potentiate GIIS (23). It was also reported that F-actin is not essential in the metabolic amplifying pathway of GIIS, using cytochalasin B, latrunculin B, and jasplakinolide (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…F-actin negatively regulates exocytosis via binding and blocking Syntaxin 4 accessibility (Jewell et al, 2008). But further studies indicate that metabolic amplifying pathway increases both phases of insulin secretion and is independent on actin microfilaments (Mourad et al, 2010).…”
Section: Insulin Biosynthesis and Insulin Exocytosismentioning
confidence: 95%
“…[26][27][28] An experiment using intact islets shows that the increase in insulin secretion produced by actin (de)polymerizing drugs was not accompanied by an increase in [Ca 2+ ] i . 29 These findings suggest that actin remodeling affects insulin secretion by mechanisms dissociated from the rise in [Ca 2+ ] i .…”
mentioning
confidence: 94%